Advances in the Study of CircRNAs in Tumor Drug Resistance - Wang, Song; Qian, Long; Cao, Tingting; Xu, Li; Jin, Yan; Hu, Hao; Fu, Qingsheng; Li, Qian; Wang, Ye; Wang, Jiawei; Xia, Yabin; Huang, Xiaoxu (Frontiers in Oncology, 2022)
Recent studies have revealed that circRNAs can affect tumor DNA damage and repair, apoptosis, proliferation, and invasion and influence the transport of intratumor substances by acting as miRNA sponges and transcriptional regulators and binding to proteins in a variety of ways. However, research on the role of circRNAs in cancer radiotherapy and chemoresistance is still in its early stages. Chemotherapy is a common approach to oncology treatment, but the development of tumor resistance limits the overall clinical efficacy of chemotherapy for cancer patients. The current study suggests that circRNAs have a facilitative or inhibitory effect on the development of resistance to conventional chemotherapy in a variety of tumors, suggesting that circRNAs may serve as a new direction for the study of antitumor drug resistance. In this review, we will briefly discuss the biological features of circRNAs and summarize the recent progression of the involvement of circRNAs in the development and pathogenesis of cancer chemoresistance.